Comparison of clinicopathological traits and prognostic factors of hepatocellular carcinoma with and without cirrhotic background. (19th March 2020) - Hu, Jian; Zhang, Zhi-Qing; Zhu, Wei; Wu, Zhen-Ru; You, Yu; Liu, Yan; Su, Dai-Wen; Wang, Yun-Bing; Gong, Jian-Ping
Abstract: The difference of the patients bearing hepatocellular carcinoma (HCC) with and without cirrhosis at clinical level has not been completely determined. This study compared their differences in clinicopathological traits and prognostic factors for relapse-free survival (RFS) and overall survival (OS). Animal model was established to validate the result of clinical observation. As a result, 82 patients bearing HCC with no cirrhosis (HCC-NC) and 146 patients bearing HCC with cirrhosis (HCC-C) were included. HCC-NC exhibited shorter prothrombin time and higher plasma albumin than HCC-C. In HCC-NC, satellite nodule was an independent risk factor for OS, and high γ-glutamyl transpeptidase was an independent risk factor for RFS. In HCC-C, female sex was an independent risk factor for OS. Stratified analysis showed the OS and RFS of HCC-NC were better than HCC-C in conditions like without cancer embolus (in the portal vein or bile duct), without lymphadenopathy in hepatic portal, without satellite nodule and with small or high-differentiated tumor. Animal model analysis showed HCC-NC had a higher liver/body weight ratio, less tumor count and smaller max tumor volume than HCC-C. In conclusion, clinicopathological traits and risk factors influencing postoperative OS and RFS differed between patients with HCC-C and HCC-NC. Abstract : We demonstrated that the clinicopathological traits and risk factors influencing postoperative OS and RFS differed between patients with HCC-NC and HCC-C. Moreover, this study successfully established the animal model for validation.